2020
DOI: 10.3389/fpubh.2020.567885
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Vaginal Microbiota Dysbiosis, Bacterial Vaginosis, and Aerobic Vaginitis, and Adverse Pregnancy Outcomes of Women Living in Sub-Saharan Africa: A Systematic Review

Abstract: Background: Previous studies have described the association between dysbiosis of the vaginal microbiota (VMB) and related dysbiotic conditions, such as bacterial vaginosis (BV) and aerobic vaginitis (AV), and various adverse pregnancy outcomes. There is limited overview of this association from countries in sub-Saharan Africa (SSA), which bear a disproportionally high burden of both vaginal dysbiotic conditions and adverse pregnancy outcomes. This systematic review assesses the evidence on the association betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 124 publications
1
40
0
Order By: Relevance
“…In addition, the increased risk of PROM is associated with aerobic vaginitis (p < 0.05) (44). Consistently, Naomi Juliana et al found that in Nigerian pregnant women, bacterial vaginosis is not associated with miscarriage and intrauterine growth retardation, but is associated with PROM, PTD, and low birth weight (45).…”
Section: The Vaginal Microbiota and Aposmentioning
confidence: 84%
“…In addition, the increased risk of PROM is associated with aerobic vaginitis (p < 0.05) (44). Consistently, Naomi Juliana et al found that in Nigerian pregnant women, bacterial vaginosis is not associated with miscarriage and intrauterine growth retardation, but is associated with PROM, PTD, and low birth weight (45).…”
Section: The Vaginal Microbiota and Aposmentioning
confidence: 84%
“…Donders et al observed that South African women with little or no Lactobacilli were 3.6 times more likely to have an infant with low birthweight (< 2 kg) compared to women with a high abundance of Lactobacilli [97]. Discussion on the mechanisms behind this possible causal effect of VMB dysbiosis on several adverse pregnancy outcomes were previously reviewed and are outside the scope of this review [1,98]. Nevertheless, there is a need for future studies using newer molecular diagnostic techniques to confirm these findings and determine whether low birthweight, preterm birth, or other adverse pregnancy outcomes are generally associated with maternal VMB composition in sub-Saharan African women.…”
Section: Vmb Characteristics and Pregnancy Outcomementioning
confidence: 99%
“…The exclusion criteria were de ned as follows: (1) outpatients under the legal age and (2) outpatients with clinically apparent herpes simplex infection. These selected variables were based on the literature (4,6,7,(16)(17)(18)(19)(20).…”
Section: Design and Subject Selectionmentioning
confidence: 99%
“…Ethnicity and geographical location would in uence the prevalence of vaginal infections. Several authors reported different inventory of the situation about vaginal's pathobionts, namely in Asia, Europe, Africa, and Latin America (6)(7)(8). As for Sub-Saharan Africa, Kenyon et al (2013) reported a higher prevalence of BV than other parts (9).…”
Section: Introductionmentioning
confidence: 99%